Regulation of IGF -1 signaling by microRNAs - Jung, Hwa Jin; Suh, Yousin (Frontiers in Genetics, 2015)
The insulin-like growth factor 1 (IGF-1) signaling pathway regulates critical biological processes including development, homeostasis, and aging. Dysregulation of this pathway has been implicated in a myriad of diseases such as cancers, neurodegenerative diseases, and metabolic disorders, making the IGF-1 signaling pathway a prime target to develop therapeutic and intervention strategies. Recently, small non-coding RNA molecules in ~22 nucleotide length, microRNAs (miRNAs), have emerged as a new regulator of biological processes in virtually all organ systems and increasing studies are linking altered miRNA function to disease mechanisms. A miRNA binds to 3’UTRs of multiple target genes and coordinately down-regulates their expression, thereby exerting a profound influence on gene regulatory networks. Here we review the components of the IGF-1 signaling pathway that are known targets of miRNA regulation, and highlight recent studies that suggest therapeutic potential of these miRNAs against various diseases.